2018
DOI: 10.1021/acs.accounts.8b00399
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Doping of Chemically Modified Gold-Based Superatoms

Abstract: Conspectus Atomically size-selected gold (Au) clusters protected by organic ligands or stabilized by polymers provide an ideal platform to test fundamental concepts and size-specific phenomena, such as the superatomic concept and metal-to-nonmetal transition. Recent studies revealed that these stabilized Au clusters take atomlike quantized electronic structures and can be viewed as chemically modified Au superatoms. An analogy between Au and hydrogen (H) atoms is an interesting proposal made for bare Au cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 46 publications
5
107
0
Order By: Relevance
“…Takano and Tsukuda recently developed an efficient bottom-up method using [MAu 8 (TPP) 8 ] n+ (TPP = PPh 3 ; n = 3 for M = Au; n = 2 for M = Pd, Pt) as starting material. [49][50][51][52][53] The growth and doping reactions were initiated by doping a hydride (H -) to the central, unligated M atom of the M@Au 8 (6e) core by the reaction with NaBH 4 (Fig. 4a).…”
Section: Emerging Trends In Synthesis 21 Targeted Synthesis By Transmentioning
confidence: 99%
“…Takano and Tsukuda recently developed an efficient bottom-up method using [MAu 8 (TPP) 8 ] n+ (TPP = PPh 3 ; n = 3 for M = Au; n = 2 for M = Pd, Pt) as starting material. [49][50][51][52][53] The growth and doping reactions were initiated by doping a hydride (H -) to the central, unligated M atom of the M@Au 8 (6e) core by the reaction with NaBH 4 (Fig. 4a).…”
Section: Emerging Trends In Synthesis 21 Targeted Synthesis By Transmentioning
confidence: 99%
“…However, an atomic‐level understanding of surface coordination chemistry in large nanoparticles (e.g., >1000 metal atoms) remains challenging, for two natures of nanoparticles—the poly‐disperse sizes (i.e., hard to be prepared uniformly at the atomic level), and the uncertain surface chemistry (e.g., metal–ligand interactions) . In view of this, metal nanoclusters have been served as model nanosystems, and precise molecular tools, for investigating the surface coordination chemistry at the atomic level owing to the monodisperse sizes and accurately characterized structures of these nanomaterials . Thiolates are most frequently used in protecting metallic kernels of nanoclusters; selenols, cognate derivatives of thiols by replacing the sulfur in thiols into selenium, have embodied their superiority in stabilizing metal nanoclusters and shown distinctively surface coordination mode.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, Tsukuda group reported a hydride‐doped gold cluster [Au 9 H(PPh 3 ) 8 ] 2+ recently, which was prepared by reacting the previously reported cluster [Au 9 (PPh 3 ) 8 ] 3+ with 1 mol equiv of NaBH 4 at room temperature (Figure ) . The DFT calculation on the simplified [Au 9 H(Me 3 ) 8 ] 2+ showed that the natural bond orbital (NBO) charge on the H atom is almost neutral, indicating that H contributes its 1s electron to the superatomic electron count.…”
Section: Recent Breakthroughmentioning
confidence: 99%